Racial Threat, Intergroup Contact, and School Punishment. (August 2017) - Hughes, Cresean; Warren, Patricia Y.; Stewart, Eric A.; Tomaskovic-Devey, Donald; Mears, Daniel P.
Objectives: Drawing on the racial threat and intergroup contact literatures, we explore whether (1) a school's racial or ethnic context increases school suspensions for Black, Hispanic, and White students; (2) intergroup contact among school board members reduces school suspensions for Black, Hispanic, and White students; and (3) a school's racial or ethnic context effects on school suspensions are conditioned by intergroup contact among school board members. Method: Count-dependent multilevel modeling techniques on school- and district-level measures from a representative sample of Florida middle and high schools. Results: Larger racial and ethnic student populations within schools increase the likelihood of suspensions for Black and Hispanic students while decreasing suspensions for White students. Further, higher levels of intergroup contact between Black, White, and Hispanic school board members are associated with a lower likelihood of suspensions for all students. Finally, intergroup contact between Black, White, and Hispanic school board members moderates the effects of school racial and ethnic context on school suspensions. Conclusions: Important factors are associated with school punishment for Black, Hispanic, and White students. Integrated spaces play an important role in decreasing both punishment disparities and punishment severity.